Matrix Metalloproteinases and Their Inhibitors in Chronic Obstructive Pulmonary Disease - Navratilova, Zdenka; Kolek, Vitezslav; Petrek, Martin (Archivum immunologiae et therapiae experimentalis, 2016)
Chronic obstructive pulmonary disease (COPD) is characterised by irreversible airflow limitation associated with chronic inflammation. Matrix metalloproteinases (MMPs) are proteolytic enzymes that contribute to the inflammatory response in COPD and degrade extracellular matrix components. Their enzymatic activity is inhibited by a four-member family of tissue inhibitors of metalloproteinases (TIMPs). In COPD, the MMP/TIMP network, mainly MMP-9, has been repeatedly observed to be dysregulated at both the local (lung) and systemic levels. Here, we review the findings reported in numerous cross-sectional studies with our primary focus on longitudinal observations in human COPD studies. The data from longitudinal prospective studies on the MMP/TIMP network may lead to the introduction of novel prognostic biomarkers into clinical management of COPD. We address the relationship between the systemic and local lung MMP/TIMP network in COPD patients and briefly describe the involvement of microRNAs. Finally, the role of the MMP/TIMP network in COPD treatment is discussed.
Keywords: Biomarker; Humans; regulace genové exprese enzymů; MicroRNAs; Local and systemic response; Tissue inhibitors of metalloproteinases; Matrix Metalloproteinases; tkáňové inhibitory metaloproteinas; Lung; Inflammation; Phenotype; lidé; Biomarkers; plíce; zánět; matrixové metaloproteinasy; biologické markery; Matrix Metalloproteinase 9; Tissue Inhibitor of Metalloproteinases; fenotyp; matrixová metaloproteinasa 9; prognóza; chronická obstrukční plicní nemoc; Cross-Sectional Studies; Matrix metalloproteinases; Gene Expression Regulation, Enzymologic; Pulmonary Disease, Chronic Obstructive; mikro RNA; Chronic obstructive pulmonary disease; průřezové studie; Prognosis